New insights into archaeological textiles (1000–1450AD) from the coastal region of the Atacama Desert: Preliminary evidence of a cochineal and shellfish purple dye combination - José J. Cárcamo-Vega; Marcela Sepúlveda; Edgar Casanova-González; Sebastián Gutiérrez; Alejandro Mitrani; Elard J. Dauelsberg; Álvaro E. Aliaga; Cecilia Lemp; José Luis Ruvalcaba-Sil (PLoS ONE, 2025)
A multi-instrumental and non-destructive approach was used to integrally analyze four archaeological textiles from the Pre-Columbian Playa Miller-3 funerary site (1100–1450 AD) located on the coast of the Atacama Desert. The protocol included a fiber washing process with a dilute Triton X100 surfactant to remove the excess metallic components and impurities adhered to the surface of the dyed fibers. The use of animal fibers was confirmed via optical microscopy, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Using X-ray fluorescence (XRF) and comparing the elemental profiles of washed and unwashed textile fibers with those of soils from the archaeological site, we obtained elemental information related to potential mordants used in the dyeing process and detected the presence of bromine in some textile samples. Surface-Enhanced Raman Spectroscopy (SERS) using gold nanostructures identified the use of carminic acid and suggested a dye mixture composed of cochineal (carminic acid) and shellfish purple (dibromoindigo), which has not been previously reported for the Atacama Desert. This work provides new insights into pre-Columbian ancestral knowledge involved in the textile technology of the coastal population from this southern Andean region.